Actualization Of Islamic-Based Curriculum In The Country Of Serambi Mekah, Indonesia - Yusuf, Rusli; Sanusi, Sanusi; Maimun, Maimun; Bahri, Syaiful; Yusoff, Mohd Zailani Mohd; Fajri, Iwan (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The actualization of an Islamic-based curriculum in Negeri Serambi Mecca can be understood as an effort to integrate Islamic teachings into all aspects of education in Aceh. Aceh as one of the regions in Indonesia has a long history as the center of Islamic civilization in the archipelago. Therefore, efforts to develop Islamic-based education in Aceh can be seen as an effort to strengthen Aceh's Islamic identity and develop the quality of education in this area. This study uses a qualitative research method with a case study approach. The results of the study show that the Islamic curriculum in Aceh has not yet received a real picture of how the teaching and learning process and evaluation in the Islamic curriculum are implemented and desired by the education office. In general, there are several main reasons why the Aceh curriculum is not implemented until 2022, including namely; (a) there is no systematic socialization of the contents of the Aceh curriculum (Islamic curriculum), (b) there is no specific guidebook for the implementation of the Aceh curriculum, both in terms of content, methods and implementation strategies, (c) there are no pilot schools for implementing the curriculum Aceh (pilot project), and (d) there are no Aceh curriculum learning tools yet.